Thermal Radiation Synthesis of Ultrafine Platinum Nanoclusters toward Methanol Oxidation. Issue 9 (26th June 2020) - Qiao, Yun; Liu, Yifan; Liu, Yang; Dong, Qi; Zhong, Geng; Wang, Xiang; Liu, Zhenyu; Wang, Xizheng; He, Shuaiming; Zhou, Wenqi; Wang, Guofeng; Wang, Chao; et al.
Abstract: Direct methanol fuel cells (DMFCs) are considered as a promising candidate for portable electronic devices and small electric vehicles due to their high gravimetric and volumetric energy densities. The operation of DMFCs requires efficient catalysts, especially on the anode to promote methanol oxidation reaction (MOR). To date, platinum has emerged as a chief contender for MOR. Unfortunately, most catalysts suffer from severe CO poisoning, which can passivate the catalytic surface and decrease the activity over time. Herein, a transient, thermal radiation method to synthesize ultrafine platinum nanoclusters (0.68 ± 0.13 nm) supported on carbon black (Pt NC/CB) is demonstrated. The sample demonstrates a great CO poisoning resistance and excellent activity toward MOR. The ultrafine platinum nanoclusters with increased active sites can promote the oxidation of CO at potential as low as 0.4 V. The Pt NC/CB displays an onset potential of 0.4 V and a peak current density of 1.30 mA cm −2 ECSA (electrochemical active surface area), which is superior than that of reported catalysts (0.57–1.06 mA cm −2 ECSA ), while many of the catalysts are alloys involving noble metals. This work showcases an efficient method to prepare Pt nanoclusters with high MOR activity and great CO poisoning resistance. Abstract : Ultrafine platinum nanoclusters (0.68 ± 0.13 nm) supported on carbon black (Pt NC/CB) are synthesized via a transient, thermal radiation method. The as‐synthesized Pt NC/CB with increased active sites is employed as the catalyst for methanol oxidation reaction, which displays a high catalytic activity (peak current density of 1.30 mA cm −2 ECSA ) and desirable CO poisoning resistance.